HYDRHA: Hydrogels of hyaluronic acid. New biomedical approaches in cancer, neurodegenerative diseases, and tissue engineering. (15th December 2022) - Grieco, Maddalena; Ursini, Ornella; Palamà, Ilaria Elena; Gigli, Giuseppe; Moroni, Lorenzo; Cortese, Barbara
Abstract: In the last decade, hyaluronic acid (HA) has attracted an ever-growing interest in the biomedical engineering field as a biocompatible, biodegradable, and chemically versatile molecule. In fact, HA is a major component of the extracellular matrix (ECM) and is essential for the maintenance of cellular homeostasis and crosstalk. Innovative experimental strategies in vitro and in vivo using three-dimensional (3D) HA systems have been increasingly reported in studies of diseases, replacement of tissue and organ damage, repairing wounds, and encapsulating stem cells for tissue regeneration. The present work aims to give an overview and comparison of recent work carried out on HA systems showing advantages, limitations, and their complementarity, for a comprehensive characterization of their use. A special attention is paid to the use of HA in three important areas: cancer, diseases of the central nervous system (CNS), and tissue regeneration, discussing the most innovative experimental strategies. Finally, perspectives within and beyond these research fields are discussed. Graphical abstract: Image 1